Literature Review of STEM/STEAM Teaching in Vietnam - Thi Thanh Hai, Pham; Thu, Tran Thi Hoai (VNU Journal of Science: Education Research; Vol 41 No 4, 2025)
Vietnam didn't start incorporating STEM into its curriculum until 2012. Definitions have been offered by studies using various techniques, such as STEM/STEAM teaching material, STEM teaching strategies, and STEM/STEAM subject functions. The article examines the research challenges using theoretical research methodologies and the Zakaria & Associates (2021) literature search map. Vietnamese studies that have discussed STEM/STEAM education Research methodologies typically utilized to research "STEM/STEAM education" are: Studies have released particular information relating to STEM/STEAM education and how to utilize these results in practice. Finally, the article identified which themes are infrequently discussed in STEM/STEAM education research in Vietnam, as well as some recommendations for future research.